Toward Machine-Learning-Based Decision Support in Diabetes Care: A Risk Stratification Study on Diabetic Foot Ulcer and Amputation - Schäfer, Zeinab; Mathisen, Andreas; Svendsen, Katrine; Engberg, Susanne; Rolighed Thomsen, Trine; Kirketerp-Møller, Klaus (Frontiers in Medicine, 2021)
Diabetes mellitus is associated with serious complications, with foot ulcer and amputation of limbs among the most debilitating consequences of late diagnosis and treatment of foot ulcer. Thus, prediction and on-time treatment of diabetic foot ulcers (DFU) are of great importance for improving and maintaining patients quality of life and avoiding the consequent socio-economical burden of amputation. In this study, we use Danish national registry data to understand the risk factors of developing diabetic foot ulcers and amputation among patients with diabetes. We analyze the data of 246,705 patients with diabetes to assess some of the main risk factors for developing DFU/amputation. We study socioeconomic information and past medical history of the patients. Factors such as low family disposable income, cardiovascular disorders, peripheral artery, neuropathy and chronic renal complications are among the important risk factors. Mental disorders and depression, albeit not as pronounced, still pose a higher risks in comparison to the group of people without these complications. We further use machine learning techniques to assess the practical usefulness of such risk factors for predicting foot ulcers and amputation. Finally, we outline the limitations of working with registry data sources and explain potentials for combining additional public and private data sources in future applications of artificial intelligence (AI) to improve the prediction of diabetic foot ulcer and amputation.